Autorzy:Jacek Lech, Marek Pisarski , Marcin Braun
Wydawnictwo:GWO
Rok wydania:2015
Zredukuj wyrazy podobne. 4.43 gwiazdek na podstawie 7 opinii

`a) \ ul(ul(k))+ul(a)+ul(ul(k))+ul(a)+o=2a+2k+o` 

`b) \ ul(ul(k))-ul(a)-ul(ul(k))+ul(a)-o=-o` 

`c) \ ul(ul(k))+ul(u)+ul(ul(k))+ul(u)+ł+ul(ul(k))+ul(ul(ul(a)))=a+3k+ł+2u` 

`d) \ ul(ul(k))+u-ul(ul(k))-u+ul(ul(ul(ł)))-ul(ul(k))+ul(a)=a-k+l` 

`e) \ r+ul(a)+ul(ul(b))+ul(a)+r+ul(ul(b))+ul(a)+r=3a+2b+3r` 

`f) \ r-ul(a)-ul(ul(b))+ul(a)-r+ul(ul(b))-ul(a)+r=-a+r` 

`g) \ ul(ul(b))+ul(a)+ul(ul(ul(r)))+ul(ul(b))+ul(a)+p+ul(a)+p+ul(a)=4a+2b+2p+r` 

`h) \ ul(ul(b))-ul(a)-ul(ul(ul(r)))-ul(ul(b))-ul(a)-p-ul(a)-p-ul(a)=-4a-2p-r`